2007
DOI: 10.1038/sj.eye.6702846
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glaucoma in patients with obstructive sleep apnoea—a cross-sectional case-series

Abstract: Aim To determine the prevalence of glaucoma in patients with obstructive sleep apnoea. Design Cross-sectional case series. Participants One hundred patients with moderate to severe obstructive sleep apnoea.Testing Within 48 h of the polysomnographic diagnosis of obstructive sleep apnoea, patients underwent the following tests: intraocular pressure, gonioscopy, automated perimetry, stereoscopic biomicroscopy, and fundascopic assessment for the presence of glaucomatous optic nerve changes. Main outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 17 publications
0
55
1
5
Order By: Relevance
“…37 The low prevalence in ours and Geyer et al's studies could be the effect of CPAP treatment. Whereas, most other studies reporting higher prevalence of glaucoma in OSAHS (7.2-27%) 3,[6][7][8]28,38 have investigated patients at time of referral for polysomnography and before initiation of therapy; Geyer recruited patients earlier diagnosed with OSAHS and possibly receiving treatment. The authors, however, have not mentioned the treatment status of the OSAHS patients in their report.…”
Section: Discussionmentioning
confidence: 99%
“…37 The low prevalence in ours and Geyer et al's studies could be the effect of CPAP treatment. Whereas, most other studies reporting higher prevalence of glaucoma in OSAHS (7.2-27%) 3,[6][7][8]28,38 have investigated patients at time of referral for polysomnography and before initiation of therapy; Geyer recruited patients earlier diagnosed with OSAHS and possibly receiving treatment. The authors, however, have not mentioned the treatment status of the OSAHS patients in their report.…”
Section: Discussionmentioning
confidence: 99%
“…According to some reports, the prevalence of primary open-angle glaucoma is increased in patients with OSAS. 7,8 Further, examination by perimetry revealed that the retinal nerve fiber layer of some OSAS patients with a normal visual field and no obvious optic neuropathy tended to be thin, 9 indicating that OSAS may affect the physiological structure of the optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of published reports on the link between glaucoma and sleep apnea has indicated that the prevalence of glaucoma among patients with sleep apnea ranges from 2% to 7.2% [11,14,15]. A recent cross-sectional case series suggested that as much as 27% of patients with moderate to severe sleep apnea might have glaucoma [66]. There is a lack of consensus whether the prevalence of glaucoma among patients with sleep apnea is greater than observed in the general population [15].…”
Section: Sleep Apnea and Glaucoma -Is There An Association?mentioning
confidence: 97%